Short-term results of hip prosthesis with shortening osteotomy in patients with crowe type iv dysplastic coxarthrosis - Omer Polat; Selim Sanel; Mehmet Nurullah Ermis; Can Solakoglu (Medicine Science)
Developmental hip dysplasia describes developmental abnormalities affecting the acetabulum, proximal femur, and capsule. Various surgical options, including pelvic and femoral osteotomies, are available yet degeneration and osteoarthritis may persist despite these interventions. Total hip arthroplasty with shortening osteotomy has yielded highly satisfactory results patients experiencing pain and reduced quality of life due to osteoarthritis. Crowe type 4 patients who were operated on by the same surgeon between 2010 and 2014 were included in the study. The study evaluated 14 hips from 9 female patients, aged between 42 and 52 years (mean age: 46.57±3.15 years). Each operated hip was followed up for at least 12 months. Preoperative, six-month, and one-year postoperative assessments included Harris Hip Scores, Oswestry Scale, VAS Hip and Lumbar, and SF-36 Quality of Life Indexes. Preoperative Harris hip scores (41.86±8.63) increased to 85.46±2.51 at six-months and 89.97±1.52 at one year. The mean preoperative VAS hip measurement was 8.50±0.76, while the mean postoperative six-month VAS hip measurement was 2.64±0.50 and the mean postoperative one-year VAS hip measurement was 2.14±0.36. The increase in the SF-36 quality of life index is statistically significant. The mean preoperative Oswestry measurement was 32.86±2.93, which decreased to 6.78±1.62 postoperatively and further decreased to 2.21±0.97 at one-year. The outcomes of shortening osteotomy combined with cementless total hip arthroplasty (THA) for treating pain and loss of function in patients with developmental dysplasia of the hip who do not respond to conservative treatments are highly favorable. [Med-Science 2024; 13(4.000): 873-8]